Kes positif mengikut negeri (setakat 3/2/2021,12 pm) - Malaysia, Kementerian Kesihatan (Kementerian Kesihatan Malaysia (KKM), 2021)
This item is made available on Ministry of Health Malaysia, Covid-19 homepage at http://covid-19.moh.gov.my/